2010
DOI: 10.1007/s12237-010-9276-3
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of Restoration and Management Changes in the Water Quality of a Central California Estuary

Abstract: Coastal managers and policy-makers are concerned with tracking improvements to water quality linked to management changes. Long-term water quality data acquired from two wetland areas in the upper reaches of the Elkhorn Slough estuary in central California were analyzed for signatures of land restoration or water control structure management. Post-restoration averaged NO 3 , NH 3 , and PO 4 concentrations were 50-70% less than before-restoration concentrations. Assessment of watershed-scale effects revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The estuary is part of several protected areas. All tidal lands below the mean high water (MHW) mark are part of the Monterey Bay National Marine Sanctuary (Gee et al, 2010) and adjacent lands are mostly protected open space including the 704 ha Elkhorn Slough National Estuarine Research Reserve. The 10-km main channel of the Slough is bordered by extensive intertidal salt marshes and mudflats, and several shallow water impoundments are associated with water control structures that restrict tidal exchange beneath railroad tracks along the eastern border of the estuary.…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…The estuary is part of several protected areas. All tidal lands below the mean high water (MHW) mark are part of the Monterey Bay National Marine Sanctuary (Gee et al, 2010) and adjacent lands are mostly protected open space including the 704 ha Elkhorn Slough National Estuarine Research Reserve. The 10-km main channel of the Slough is bordered by extensive intertidal salt marshes and mudflats, and several shallow water impoundments are associated with water control structures that restrict tidal exchange beneath railroad tracks along the eastern border of the estuary.…”
Section: Study Sitementioning
confidence: 99%
“…To ensure that historical differences in interpolation maps were a function of data differences rather than variogram methodology, the spherical kriging method was used for all timepoints. We also applied data from monthly water quality sampling collected by a volunteer-based monitoring program at a network of (~26) stations across Elkhorn Slough since 1988 (Ritter et al, 2008;Gee et al, 2010). Monthly nitrate data from the sites were averaged during the period 1990 to 2010 and mapped using ordinary kriging for comparison to spatial patterns of the isoscape and stoichioscape maps.…”
Section: Isoscape and Stoichioscape Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1997, the south culvert broke open and resulted in an increase in tidal range. The Elkhorn Slough National Estuarine Research Reserve (ESNERR) found a significant decrease in nitrate (NO3) within the system (samples were taken in the middle of the wetland) from before and after this accidental restoration took place (Gee et al 2010). This change in hydrology decreased nutrients in the system due to greater tidal exchange, and created a 100' vegetated buffer between adjacent agricultural fields and the high-water edge of the wetland.…”
Section: Study Area and Study Systemmentioning
confidence: 99%